FIGO postpartum intrauterine device initiative: Complication rates across six countries. (18th September 2018) - Makins, Anita; Taghinejadi, Neda; Sethi, Maya; Machiyama, Kazuyo; Munganyizi, Projestine; Odongo, Elly; Divakar, Hema; Fatima, Parveen; Thapa, Kusum; Perera, Gamini; Arulkumaran, Sabaratnam
Abstract: Objective: To record and analyze complication rates following postpartum intrauterine device (PPIUD) insertion in 48 hospitals in six countries: Sri Lanka, India, Nepal, Bangladesh, Tanzania, and Kenya. Methods: Healthcare providers were trained in counselling and insertion of PPIUD via a training‐the‐trainer model. Data were collected on methodology, timing, cadre of staff providing care, and number of insertions. Data on complications were collected at 6‐week follow‐up. Statistical analysis was performed to elucidate factors associated with increased expulsion and absence of threads. Results: From May 2014 to September 2017, 36 766 PPIUDs were inserted: 53% vaginal and 47% at cesarean delivery; 74% were inserted by doctors. Follow‐up was attended by 52%. Expulsion and removal rates were 2.5% and 3.6%, respectively. Threads were not visible in 29%. Expulsion was less likely after cesarean insertion (aOR 0.33; 95% CI, 0.26–0.41), following vaginal insertion at between 10 minutes and 48 hours (aOR 0.59; 95% CI, 0.42–0.83), and when insertion was performed by a nurse (aOR 0.33; 95% CI, 0.22–0.50). Conclusion: PPIUD has low complication rates and can be safely inserted by a variety of trained health staff. Given the immediate benefit of the one‐stop approach, governments should urgently consider adopting this model. Abstract : The FIGO PPIUD initiative demonstrated expulsion and removal rates of under 5% after follow‐up of 52% of 36 766 PPIUD insertions across six countries.